2016
DOI: 10.1136/gutjnl-2015-311004
|View full text |Cite
|
Sign up to set email alerts
|

Primary sclerosing cholangitis is characterised by intestinal dysbiosis independent from IBD

Abstract: ObjectivePrimary sclerosing cholangitis (PSC) is a chronic cholestatic liver disease often leading to end-stage liver disease. Its pathogenesis remains largely unknown, although frequent concomitant IBD hints towards common factors underlying gut and bile duct inflammation. Considering the mounting evidence on the involvement of the intestinal microbiota in initiating and determining IBD phenotype, we investigated intestinal microbiota composition in patients with PSC.DesignStool samples were collected from 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
293
3
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(323 citation statements)
references
References 40 publications
23
293
3
4
Order By: Relevance
“…In summary, this first PSC study observed a clear gut signature in PSC distinct from healthy controls and patients with UC without liver disease suggesting that the intestinal microbiota (IM) could reflect a relevant player in PSC. These findings are strengthened by another recently published study where authors also observed an increase in Veilonella species 62 . Veilonella has been associated with other chronic inflammatory disorders including fibrotic conditions and liver cirrhosis where subjects have higher colonic Veilonella levels 63.…”
Section: Primary Sclerosing Cholangitis and Microbiotasupporting
confidence: 65%
“…In summary, this first PSC study observed a clear gut signature in PSC distinct from healthy controls and patients with UC without liver disease suggesting that the intestinal microbiota (IM) could reflect a relevant player in PSC. These findings are strengthened by another recently published study where authors also observed an increase in Veilonella species 62 . Veilonella has been associated with other chronic inflammatory disorders including fibrotic conditions and liver cirrhosis where subjects have higher colonic Veilonella levels 63.…”
Section: Primary Sclerosing Cholangitis and Microbiotasupporting
confidence: 65%
“…13 In summary, in this exploratory study, patients with PSC-IBD had a distinct stool BA and stool microbiota composition, as well as specific microbiota-stool BA correlations when compared with IBD. Whether these changes are associated with or may predispose to the specific PSC-IBD phenotype including the increased risk of colorectal neoplasia needs to be further clarified and warrants further research.…”
Section: Discussionmentioning
confidence: 67%
“…Murine model studies of type I diabetes indicate that gender bias may be influenced by the gut microbial community through its interaction with sex hormones, although the underlying mechanisms are poorly characterised 38 39. In contrary to PBC, no significant difference in gut microbiome has been observed between patients with PSC taking UDCA and those not 14. This coincides with the distinct therapeutic efficacy of UDCA in PBC and PSC.…”
Section: Discussionmentioning
confidence: 82%